Predictive fatigue life modelling for aluminum alloys winder high temperature and shot peening interact - Allawi H. Alwin; Hatem Ksibi (Frontier Materials & Technologies)
Enhancing the surface quality of shells subjected to high stress is a major task. A variety of procedures are employed for dealing with this issue. Shot peening is particularly common for aluminium alloys made. In fact, the main method for assessing the surface’s durability under consideration is fatigue testing using standard specimens over several cycles. This paper investigates the performance of aluminium alloys under high-temperature exposure, examining their behaviour with and without shot peening-induced hardening. In fact, the study focuses on the fatigue behaviour of aluminium alloys 2024-T4 and 2024-T361 at 250 °C. Experiments on standard-sized specimens were conducted at both room temperature and 250 °C to evaluate how temperature affects fatigue life. The findings were consistent with previously published data, providing useful insights into the behaviour of these alloys at extreme temperatures. Additionally, a mathematical model was developed, integrating the Stress – Number of cycles curve, loading sequence, temperature, and surface hardness from shot peening. This model was compared with Miner’s rule to assess its predictive accuracy. The results show that the new model provides more accurate predictions of fatigue life than Miner’s rule, thereby improving the reliability and safety of components in high-temperature applications. By offering precise fatigue life predictions, this research aids in the design and development of more durable aluminium alloy components, ensuring optimal performance and safety in challenging operating environments.